Learning to learn – using self-awareness of learning styles to promote language learning - Nunes, Vanessa Matos Dias (2018)
The present study was developed as part of the practicum of my master’s degree in teaching English as a foreign language (EFL) in primary school with the aim of understanding of the concepts of metacognition and self-awareness of learning styles to promote language learning. Another aim of the study was to determine and develop differentiated tasks related to personal learning styles within the daily context of learning. The participants were 25, 4th form students aged between 9 and 10 years old. Action research was the methodology applied in this one class environment which comprised both qualitative and quantitative data collection by means of questionnaires, visual aids, teaching journals and weekly reflections for the Seminário de Orientação da Prática Supervisionada 2 (SO PES2), one of the Master degree courses. Results were debated through open class discussion and reflective questioning, that is, students were encouraged to share their opinions on learning styles and learning strategies as a means to develop self-awareness of these. The study demonstrated that young learners are able to reflect on learning preferences and to critically analyse their learning styles thus gaining a deeper understanding of themselves as learners. This also allowed them to develop strategies to deal with their strengths and weaknesses.